Pemeriksaan Angka Kuman Alat Makan Pada Pedagang Kaki Lima di Jakabaring Sport City Palembang - Rahmi Garmini (IKesT Muhammadiyah Palembang, 2025)
Background: The bacterial count is a calculation of the number of bacteria based on the assumption that each living bacterial cell will grow into a colony after incubation in a suitable culture medium. Objectives: This study aimed to examine the number of germs on bowls and spoons from eight street vendors at Jakabaring Sport City Palembang. Method: This study used the method using the total plate count (ALT) method with swab sampling. Population: 8 Street Vendors in Jakabaring Sport City Palembang. Sample: 20 samples of cutlery. Results: The results showed that the cleanliness of most traders does not meet health standards. Only spoons from two traders (C and F) meet the requirements with a germ count of less than 100 colonies/m², while six other traders (A, B, D, E, G, H) have spoons with a germ count exceeding 100 colonies/m². For bowls, only one trader (B) has a bowl that meets the requirements with a germ count of less than 100 colonies/m². Seven other traders (A, C, D, E, F, G, H) have bowls with a germ count exceeding 100 colonies/m². Conclusion: The practice of eating utensil hygiene among street vendors in Jakabaring Sport City needs to be improved to ensure consumer health.